PENGARUH LINGKUNGAN KERJA, KOMITMEN ORGANISASI, KEPUASAN KERJA DAN KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN KONAWE - Yu nila (Jurnal Akrab Juara, 2019)
This study aims to determine the magnitude of the Effect of Work Environment, Organizational Commitment, Job Satisfaction and Leadership on the Work Discipline of Employees of the Regional Financial and Asset Management Agency of Konawe Regency.The population in this study were all civil servants who worked in the office of the Regional Financial and Asset Management Agency of Konawe Regency, amounting to 69 people. The sampling technique uses saturated samples so that the number of respondents is 69 people. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that work environment variables have a negative and insignificant effect on work discipline, organizational commitment variables have a positive and significant effect on work discipline, job satisfaction variables have a negative and significant effect on work discipline, and leadership variables have a positive and significant effect on work discipline